The birds of Elazig region - Ayvaz, Y. (My University, 1993)
Elazig city is situated in the eastern part of Anatolia; 169 bird species are listed. -from English summary
Elazig Bolgesi kuslari
Keywords: Anatolia; Elazig; Turkey; avifauna; bird